The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1159/000446363
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses of the Immature Annulus Fibrosus to Dynamic Compression in a Disc Perfusion Culture

Abstract: Mechanical stimuli participate in disc development and remodelling. However, the effects of mechanical load on the immature annulus fibrosus (AF) are largely unclear. This study aimed to investigate how the immature AF responded to dynamic compressive magnitude and duration. Immature porcine discs were bioreactor-cultured for 7 days and then dynamically compressed at various magnitudes (0.1, 0.2, 0.4, 0.8 and 1.3 MPa at a frequency of 1.0 Hz for 2 h/day) and durations (1, 2, 4 and 8 h/day at a magnitude of 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Excessive compressive loading is regarded as a negative external factor for disc biology [ 48 ]. In line with this opinion, our previous study also demonstrated that a high compressive magnitude induced degenerative changes within the disc tissue, such as decreased matrix biochemical content, upregulated matrix degrading enzymes and downregulated matrix genes and tissue inhibitors of matrix metalloproteinase [ 42 , 46 , 49 ]. Together, the attenuated matrix homeostatic phenotype of NP cells under high-magnitude compression also indirectly suggests that high-magnitude compression promotes NP cell senescence.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Excessive compressive loading is regarded as a negative external factor for disc biology [ 48 ]. In line with this opinion, our previous study also demonstrated that a high compressive magnitude induced degenerative changes within the disc tissue, such as decreased matrix biochemical content, upregulated matrix degrading enzymes and downregulated matrix genes and tissue inhibitors of matrix metalloproteinase [ 42 , 46 , 49 ]. Together, the attenuated matrix homeostatic phenotype of NP cells under high-magnitude compression also indirectly suggests that high-magnitude compression promotes NP cell senescence.…”
Section: Discussionsupporting
confidence: 67%
“…Eighteen healthy experimental animals (Sprague-Dawley rats, male, 320–340 g, 12 weeks old) were maintained in standard housing and husbandry conditions before starting this study. The lumbar discs (L1–L5) were harvested as described in a previous study [ 42 ]. Then, the discs were cultured for 10 days in the tissue culture chamber of our self-developed bioreactor and compressed at a magnitude of 0.1 or 1.3 MP (1.0 Hz, 6 hours per day).…”
Section: Methodsmentioning
confidence: 99%
“…IDD largely contributes to low back pain [3]. As a mechanical element of the spine, it is subjected to various mechanical stimuli during daily activities [7,19,20]. It has been established that mechanical overload is an important pathological factor to initiate and aggravate disc degeneration [13–15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and our own investigations have demonstrated that mechanical compression has an important role in regulating disc NP cell biology [18-21]. To investigate effects of mechanical compression on the matrix production of 3D-cultured NP cells, we analyzed for the first time the expression of NP cell-specific markers (keratin-19, FOXF1 and PAX1) under mechanical compression.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the disc NP cells are subjected to various kinds of mechanical compression [17], which have a great influence on disc NP cell biology, including cell phenotype and matrix biosynthesis [18-21]. Among the types of mechanical loads, static compression and dynamic compression have usually been applied in the research field of disc degeneration [22-24].…”
Section: Introductionmentioning
confidence: 99%